Sales Effectiveness at PT. Angkasa Pura - Saputra, Hendra; Sari, Ayu Kurnia (International Conference on Sciences Development and Technology, 2023)
Functional review is an administrative tool aimed at reducing asset misuse. The first step in the Operational Audit process is to see whether activities exist or not, find areas that can be improved, then create measurable performance standards for each activity. A service or product will be sold by a company. The process of selling a company's services or products is known as sales. This research aims to show empirically that the sales effectiveness of PT. Angkasa Pura II can be improved through operational audits. This research is quantitative. consequences of this exploration. There was no interaction between variables in this study. The importance of this influence is demonstrated by previous research. A functional review alone is sufficient, this must be seen from the ability of the examiner, the review program that has been completed is prepared first before the functional review is carried out, so that the functional review carried out is a functional review carried out to achieve the stated objectives. Objectively, because PT is the company, this research has no effect. The reason is, the Lintasit Angkasa Pura II branch does not sell products, but rather a service business.